Intellectual/developmental disabilities among people incarcerated in federal correctional facilities in Ontario, Canada: Examining prevalence, health and correctional characteristics. Issue 3 (26th March 2022) - Matheson, Flora I.; Dastoori, Parisa; Whittingham, Lisa; Calzavara, Andrew; Keown, Leslie A.; Durbin, Anna; Kouyoumdjian, Fiona G.; Lin, Elizabeth; Volpe, Tiziana; Lunsky, Yona
Abstract: Background: There is little research with people who experience intellectual/developmental disabilities and imprisonment. Methods: The study linked health and correctional data to examine prevalence of intellectual/developmental disabilities and health and correctional characteristics among adults experiencing their first federal incarceration between 1 January 2002 and 31 December 2011 ( n  = 9278) and two non‐incarcerated groups ( n  = 10, 086, 802). Results: The prevalence of intellectual/developmental disabilities was 2.1% in the incarcerated group and 0.9% in the non‐incarcerated group. Before incarceration, those with, versus without, intellectual/developmental disabilities were at greater risk of traumatic brain injury, mental illness, and substance use disorders. While incarcerated, those with intellectual/developmental disabilities were more likely to incur serious institutional disciplinary charges. Post‐incarceration, persons with intellectual/developmental disabilities were at greater risk of emergency department visits, and psychiatric and acute hospitalizations, than the non‐incarcerated groups. Conclusions: People with intellectual/developmental disabilities are overrepresented in Canadian federal correctional institutions. The authors offer strategies to support people prior to, during, and post‐incarceration.